2022
DOI: 10.1371/journal.pone.0263720
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV testing among youth aged 15–24 years in The Gambia

Abstract: Background Worldwide, an estimated 38.0 million people lived with the human immunodeficiency virus in 2019, and 3.4 million young people aged 15~24 years were living with HIV. Sub-Saharan Africa carries a significant HIV burden with West and Central Africa most affected with HIV. Among the young people living with HIV in West and Central Africa, an estimated 810,000 were aged 15~24 years. This study aimed to assess predictors that influence the uptake of HIV testing among youth aged 15~24 years in The Gambia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 45 publications
(104 reference statements)
5
16
4
Order By: Relevance
“…Our study found a significantly lower prevalence of HIV testing among young men than in studies conducted in Nigeria [40] and the Gambia [41]; however, these findings contributed to a better understanding of the current HIV prevention challenges among young men in PNG.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Our study found a significantly lower prevalence of HIV testing among young men than in studies conducted in Nigeria [40] and the Gambia [41]; however, these findings contributed to a better understanding of the current HIV prevention challenges among young men in PNG.…”
Section: Discussioncontrasting
confidence: 76%
“…Our study found a significantly lower prevalence of HIV testing among young men than in studies conducted in Nigeria [40] and the Gambia [41]; however, these findings contributed to a better understanding of the current HIV prevention challenges among young men in PNG. The low rates of HIV testing found in this study show only a minimal decrease in the HIV testing uptake in this age group when compared to the country’s recent data [39].…”
Section: Discussioncontrasting
confidence: 73%
“…18,[34][35][36][37][38][39] Conversely, a systematic review carried out in sub-Saharan Africa in addition to other crosssectional studies conducted in the Gambia and South Africa reported higher odds of self-reported optimal adherence among the female respondents compared to their male counterparts. 29,31,40 However, there was no observed statistically significant gender difference between self-reported adherence and socio-demographic variables in studies conducted in Togo, Cameroun, Malawi and the United States of America. 27,33,39,41 Furthermore, variables such as; level of education, religion and HIV/AIDS support services were statistically significantly associated with self-reporting optimal adherence only among the male group.…”
Section: Discussionmentioning
confidence: 88%
“…32,[35][36][37][38] Although, two other studies carried out in Nigeria and Cameroun showed no statistically significant association between the variables of interest in between male and female gender. 39,40 This implies that gender may play a vital role in self-reporting of medication adherence.…”
Section: Discussionmentioning
confidence: 99%